With Masses and Arms : Peru's Tupac Amaru Revolutionary Movement - La Serna, Miguel (Book collections on Project MUSE., 2020)
"Miguel La Serna's gripping history of the Tupac Amaru Revolutionary Movement (MRTA) provides vital insight into both the history of modern Peru and the link between political violence and the culture of communications in Latin America. Smaller than the well-known Shining Path but just as remarkable, the MRTA emerged in the early 1980s at the beginning of a long and bloody civil war. Taking a close look at the daily experiences of women and men who fought on both sides of the conflict, this fast-paced narrative explores the intricacies of armed action from the ground up"--